Synthesis and characterization of magnesium doped biphasic calcium phosphate - A R, Toibah; Sopyan, Iis; Mel, Maizirwan (Malaysian Medical Association, 2008)
The incorporation of magnesium ions into the calcium phosphate structure is of great interest for the development of artificial bone implants. This paper investigates the preparation of magnesium-doped biphasic calcium phosphate (Mg-BCP) via sol gel method at various concentrations of added Mg. The effect of calcinations temperature (ranging f rom 500"C to 900'C) and concentrationso f Mg incorporatedi nto BCPh asb eens tudied by the aid of XRD, TGA and infrared spectroscopy (lR) in transmittance mode analysis, The study indicated that the powder was pure BCPa nd Mg-BCPw ith 100o/op urity and high crystallinity. The results also indicated that B-tricalcium phosphate( F-TCPp) hasec an be observedw hen the powder was calcineda t 800oCa nd above.